Effects of rhubarb peony decoction combined with antibiotics in treating pediatric periappendiceal abscess - Lin, Zhixiong; Zeng, Huiping; Cai, Shujie; Chen, Fei; Wang, Xiang; Wu, Dianming; Liu, Mingkun; Fang, Yifan (Frontiers in Pediatrics, 2023)
Background/Purpose Rhubarb Peony Decoction (RPD) is a formula of traditional Chinese medicine, which has been widely used for the treatment of intra-abdominal inflammatory diseases. To investigate the therapeutic efficacy of RPD in pediatric periappendiceal abscess, patients having received intravenous antibiotic alone were hereby compared with those treated with intravenous antibiotic combined with RPD. Methods A retrospective review of children with periappendiceal abscess who received conservative treatment in our hospital between January 2013 and April 2022 was performed. The patients were divided into the intravenous antibiotic group (the control group) and the intravenous antibiotic combined with RPD group (the intervention group). Interval appendectomy (IA) was generally performed 10-12 weeks after conservative treatment. The primary outcome was the cure rate of conservative treatment, while the secondary outcomes included the recurrence rate, days of total intravenous antibiotics use, length of hospital stay (LOS), postoperative complications, and the liver injury caused by RPD. Results A total of 142 patients (77 females and 65 males) were included, 52 in the control group and 90 in the intervention group. The two groups were similar in demographic data and clinical characteristics (P>0.05). The mean total course of RPD in the intervention group was 11.82 days. Intervention group had a significantly higher cure rate than the control group (93.33% vs. 80.77%, P = 0.029), but the days of total intravenous antibiotics use (P = 0.150), LOS (P = 0.077) and the recurrence rate (9.52% vs. 4.76%, P = 0.439), also the operative time (P = 0.101), LOS (P = 0.572) and postoperative complications (P = 0.549) were not significantly difference between the two groups when the patients received IA. No patient had liver injury caused by RPD during the treatment. Conclusion Intravenous antibiotic combined with RPD demonstrated high effectiveness and safety for treating pediatric periappendiceal abscess.